Monomachus (Hymenoptera, Monomachidae) from Atlantic rainforests in Sao Paulo State, Brazil - Perioto, Nelson W. [UNESP]; Lara, Rogeria I. R.; Fernandes, Daniell R. R.; De Bortoli, Caroline P. [UNESP]; Salas, Claudio [UNESP]; Netto, Jacob Crosariol [UNESP]; Perez, Lumey A. [UNESP]; Trevisan, Maira [UNESP]; Kubota, Mirian M. [UNESP]; Pereira, Nirelcio A. [UNESP]; Gil, Oniel J. A. [UNESP]; Dos Santos, Rafael F. [UNESP]; et al. (Soc Colombiana Entomologia-socolen, 2016)
A survey of Monomachus (Hymenoptera, Monomachidae) was carried out with five Malaise traps/area in five areas of Atlantic Rainforest in Sao Paulo State, Brazil. The sampling effort in all localities amounted to 9,900 traps-day. Data were obtained from a total of 304 exemplars of Monomachus: 66 females and 238 males. The highest occurrence of Monomachus was observed between June and September with a frequency peak in July, and they were most frequent in Parque Estadual Morro do Diabo (PEMD) (350 m above sea level), where the sampling effort to catch each exemplar was 65.1 traps-day. From the sample of females of Monomachus captured in the Parque Estadual Intervales, Parque Estadual da Serra do Mar/Nucleo Santa Virginia (PESM/NSV), PEMD and Estacao Ecologica Jureia Itatins, between December 2009 and December 2010, two species were recognized: M. fuscator (N = 58 / 87.9 %) and M. cubiceps (8 / 12.1 %). In additional samplings in 2011 at PESM/NSV two exemplars of M. klugii recorded only from Rio de Janeiro State, Brazil were obtained, showing that its distribution has extended to Sao Paulo State.
Keywords: Chiromyzinae; Diaprioidea; Malaise trap; Neotropical; Parasitoids